Narratives of Students and Teachers in a Public School: Perspectives Based on the Ethics of Care; [Narrativas de Estudiantes y Docentes en Una Escuela Pública: Miradas Desde la Útica del Cuidado] - Winkler-Muller, M; Jorquera-Martinez, C (Universidad Austral de Chile, 2023)
The ethics of care is revealed as an indispensable framework for the configuration of inclusive school cultures and well-being. The qualitative results of a pilot study carried out in a municipal school in Santiago de Chile are presented, the objective of which was to reconstruct the narratives on practices and experiences of the concept of care, through interviews and face-to-face discussion groups, in a pre-pandemic context. From an intersubjective analysis and open categorization, four central categories in relation to care were inductively elaborated: context, conceptualization of care, care and non-care practices. From a relational analysis, a hypothetical-comprehensive model was developed, based on care conceived as protection. It is concluded that care appears vaguely defined, an unrecognized task and that it stresses the relationships between the members of the community. This diagnosis constitutes a relevant precedent for the new challenges that will have to be faced in the post-pandemic context. © 2023, Universidad Austral de Chile. All rights reserved.